1992
DOI: 10.1139/l92-036
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of transversely loaded continuous steel–concrete composite plates: experimental program and test results

Abstract: It is apparent from a review of the literature and current research related to the design of ice-resisting walls for offshore structures that there is a need for more efficient designs of these structural elements. The object of this study was to examine an alternate structural element for ice-resisting walls, a flexible composite plate system, which is simple in detail, design, and construction and utilizes the capacity of the section.An exploratory experimental program was undertaken to determine the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Steel-concrete interface friction tests were carried out by Kennedy and Cheng [9], and it was found that the mean value of the kinetic coefficient of friction µ was 0.5 with a coefficient of variation of 0.15. An elastic parametric study described in Ref.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Steel-concrete interface friction tests were carried out by Kennedy and Cheng [9], and it was found that the mean value of the kinetic coefficient of friction µ was 0.5 with a coefficient of variation of 0.15. An elastic parametric study described in Ref.…”
Section: Finite Element Analysismentioning
confidence: 99%